Loneliness among mothers raising children under the age of 3 years and predictors with special reference to the use of SNS: a community-based cross-sectional study - Marie Mandai; Misato Kaso; Yoshimitsu Takahashi; Takeo Nakayama (BMC, 2018)
Abstract Background Loneliness in mothers raising children can adversely impact the health of their children and lead to child abuse, depression, and deterioration of mothers' health. Few studies to date have specifically assessed the association between loneliness and social factors, including the use of social network sites (SNSs), and personal factors. This study aimed to identify predictors of loneliness in mothers raising children, with special reference to SNS use. Methods This cross-sectional study involved an anonymous self-reported questionnaire survey of mothers participating in the health check-ups for their children in Nagahama City, Japan, from July 28 to September 29, 2014. The following items were assessed: revised UCLA Loneliness Scale, "Secure" subscale of the Internal Working Model Scale (IWMS-S), psychological distress scale (K6), abbreviated Lubben Social Network Scale (LSNS-6), and types of communication devices and information sources. Multiple regression analysis was performed using the Loneliness Scale score as the dependent variable. Results Among 763 mothers attending health check-ups for children in Nagahama City, 715 were available for the survey. Among a total of 638 respondents, data from 523 mothers were analyzed (valid response rate: 73.1%). The mean Loneliness Scale score ± standard deviation was 36.1 ± 9.7. The multiple regression analysis revealed that loneliness was significantly associated with being financially worse-off (β = − 3.35, p = 0.004) and struggling (β = − 2.47, p = 0.047); having a smaller family social network (β = − 0.32, p = 0.032), having fewer friends (β = − 0.49, p = 0.001), and having a smaller SNS network (β = − 0.21, p = 0.018); a lower secure subscale score on the IWMS-S (β = − 0.56, p < 0.001); and a K6 score of ≥5 (β = 4.24, p < 0.001). Conclusion The degree of loneliness in mothers raising children was associated with a smaller social network, lower secure attachment style, and a higher possibility of psychological distress. These factors should be considered when developing effective interventions against loneliness in mothers raising children.